A Critical Regionalist Reading of The Brief Wondrous Life of Oscar Wao: Rethinking Magical Realism through Afro-Caribbean Oral Narrative. (29th April 2019) - Winstein-Hibbs, Sarah
Abstract: This article examines the use of regional oral narratives in Junot Díaz's The Brief Wondrous Life of Oscar Wao (2007) and makes a case for coupling "global, " transnational, or hemispheric readings of this text with a rich sense of regional and local cultural forms. While scholarship has primarily analyzed the novel's fantastic figures (such as the mongoose and faceless man) through the broad lens of magical realism, my study reads these figures in relation to Caribbean popular culture. And while many critics have inquired into the text's engagement with other written genres, few have thoroughly examined its use of Caribbean oral narrative. I trace the historical roots of the oral narratives invoked by the book, and I inquire into the way Oscar Wao refashions these narratives as metaphors for contemporary sexual economies in the Americas. This allows me to return to a pressing topic of criticism on the book, but through a new lens: many scholars note that while the narrator, Yunior, engages in the ethical work of subaltern historiography, he also takes his cue from the dictator Trujillo, wielding undue power over the bodies of his characters. In this article, I ask whether Yunior's unstable ethical role, verbal agility, and candid critique of power may also descend from specifically Caribbean strategies of oral performance. Oscar Wao has quickly and firmly established itself within the high cultural space of the academy. As its institutional popularity grows, it is important to ask how this book situates itself in relation to working-class, local, and "folk" cultural forms.